2014
DOI: 10.4103/0377-4929.142639
|View full text |Cite
|
Sign up to set email alerts
|

CD10-A new prognostic stromal marker in breast carcinoma, its utility, limitations and role in breast cancer pathogenesis

Abstract: This study gives substantial proof to the various models/research papers explaining the role of stroma/CD10 in breast cancer pathogenesis. Keeping the role stroma plays in predicting prognosis and tumor response, CD10 should be included as a routine pre-chemotherapy marker in breast carcinoma. Further studies should be performed to see the role stroma plays in hormonal expression and the usefulness of CD10 to predict treatment failure in breast carcinomas receiving neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 26 publications
11
39
0
2
Order By: Relevance
“…16 Jana SH et al also observed similar results. 9 In the present study 73% (22 out of 30) of the cases showed positivity for CD10 in the stroma, of which 46% (14) cases were strongly positive and 27% (8) were weakly positive. Only two cases of strong positivity for CD10 were noted in the adjacent normal breast parenchyma.…”
supporting
confidence: 49%
See 4 more Smart Citations
“…16 Jana SH et al also observed similar results. 9 In the present study 73% (22 out of 30) of the cases showed positivity for CD10 in the stroma, of which 46% (14) cases were strongly positive and 27% (8) were weakly positive. Only two cases of strong positivity for CD10 were noted in the adjacent normal breast parenchyma.…”
supporting
confidence: 49%
“…CD10 act as a stem cell regulator in the breast and prevents uncontrolled proliferation of stem cells. 9 In most of the normal breast tissue, except a small population of stromal cells has been shown to express CD10, there are no CD10 positive stromal cells. 16,17 In gastric carcinoma, CD10 positive stromal cells are correlated with vascular invasion and metastasis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations